A expansão do REUNI na UFPB/CAMPUS I e os impactos no Centro de Ciências Sociais Aplicadas (2006 – 2015) - Diniz, Edileuda Soares (2020)
The research analyses the Programa de Reestruturação e Expansão das Universidades Federais (REUNI) [Program for Restructuring and Expansion of Federal Universities] in its expansion process at Universidade Federal da Paraíba (UFPB), in the the Social and Applied Sciences Centre (CCSA) in where is questioned the implications and impacts produced in the administrative and academic scope of this Teaching Centre. For that, the objective is to analize the REUNI planning and implementing process in the period between 2006-2015 from the acession of UFPB to REUNI, highlighting the infrastructure investments; expansion of enrolment and academic and curricular monitoring of on-campus education. The research is based on the qualitative approach using quantitative data by the theoretical perspective of the Phenomenological approach in which the Policy of Expansion category appears as the central in data analysis, and the categories Higher Education and Expansion are empirical from the research locus. As methodological procedures the documental analysis from institutional and official documents about CCSA/UFPB expansion was adopted; semi structured interview with eight teachers that forms the study sample.The research data indicate that the REUNI impact in the scope of CCSA/UFPB is linked to the recast proposal, both in the Centre infrastructure restructuring as in the academic-curricular management, that contributed with improvements in physical environment as well as the effectiveness of professional formation in the graduation level. Nevertheless, the interviewed point out paper and administration problems, in which the teacher has got his activities demands in addition to teaching, research and extension, that caused excessive increase of their teaching bureaucracy functions.